Physical properties of sausage analogues made with quinoa and cañihua flours, by extrusion - Aviles , Jordan; Leon , Alicia; Medina , Wenceslao (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Sausages are widely consumed meat products around the world. The objective of this research was to evaluate the physical properties (color, texture, cooking performance, diameter reduction) and acceptability of sausage analogues prepared from meat analogues using high-moisture extrusion. Two sausage analogues were prepared, including mixtures of quinoa flour (QF) and cañihua flour (KF) with soy protein isolate in different proportions, SA-1 (15 % QF, 15 % KF) and SA-2 (25 % QF, 15 % KF). Color was evaluated by image analysis; texture by texture profile analysis; cooking yield and diameter reduction by weight and dimension ratios. For comparison purposes, commercial chicken and pork sausages were used. SA-1 had a hardness of ~64 N, ~0.30 cohesiveness, ~0.65 elasticity, and ~14 N chewiness, values similar to chicken sausages. The color of SA-1 and SA-2 was similar to chicken sausages, with a hue of ~318° and saturation between 12.54 and 15.89 %. The cooking yield of SA-1 was ~93 %, higher than that of commercial sausages (~86 %). Sensory evaluation of SA-1 was comparable to that of pork and chicken sausages. SA-1 had physical properties similar to commercial chicken sausages, demonstrating the possibility of producing this type of product.